أثر وعي المُزارعين في التعامل مع مستلزمات وقاية النبات ( مُزارعي البيوت البلاستيكية في الساحل السوري ) - مخول مخائيل (Latakia University Journal -Biological Sciences Series, 2013)
This research aims to study the social and economic aspects of workers in protected agriculture, specifically greenhouse workers, in addition to the impact of these aspects on the safe treatment of various plant protection tools like pesticides, and the appropriate scientific methods of using them. For this purpose, 110 questionnaires were distributed among Greenhouse farmers in Tartous and Lattakia governorates. This is due to the excessive usage of insecticides by the farmers in those areas which could reach p to 22 times in one agricultural season (Statistical office Lattakia – 2010 ). Neither the source nor the origin of most of used insecticides is known. Naturally they may have bad effects on humankind and the environment. Many results were reached by this study. First, Greenhouse agriculture is a factor for social stability for 86% of farmers, all of whom are educated. 86.4% of farmers know nothing about the effects of the insecticides on man (paralysis or blindness). Only 17.8% have good knowledge of insecticide injuries, and 60.2% were neutral to their negative effects. 24.8% of farmers follow protection steps, while about 50% do not use a scientific method to get rid of the insecticide residues. 91.8% of farmers depend on high pressure sprayers with hoses and spraying guns. 56.4% were ready to replace the sprayers used with others that posed less harm on environment, but on the condition that these new sprayers should be effective and cheap. This research also showed that farmers’ source of information about plant protection was agricultural pharmacies and Guidance Centers.